Pendalaman Dan Pengembangan Materi Pendidikan Agama Islam Bidang Al-Quran Di Madrasah Aliyah - Aprina Noor Latifah; Nisa Muflihah; Nor Laila; Hasni Noor (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This study explores the deepening and development of Islamic Religious Education (IRE) materials in the field of Al-Qur'an studies at Madrasah Aliyah. The research aims to identify the effectiveness, relevance, and implementation of Al-Qur'an learning materials in enhancing students' understanding, interpretation skills, and Qur'anic literacy. Using a qualitative approach-including literature review, curriculum analysis, and interviews with teachers-the study examines how instructional strategies, learning resources, and assessment methods are applied in classrooms. The findings reveal that while the existing curriculum provides a solid foundation, further enrichment is needed to accommodate students' diverse learning needs and to integrate contemporary issues within Qur'anic studies. The research recommends curriculum refinement, the development of innovative learning modules, and the incorporation of technology-assisted learning to improve students' engagement and mastery of Al-Qur'an material. This study contributes to efforts in strengthening Islamic education by offering insights into more comprehensive and contextualized Qur'anic learning at the senior secondary level.